2022
DOI: 10.2172/1868329
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Wind Energy Futures Study

Abstract: This report is available at no cost from the National Renewable Energy Laboratory (NREL) at www.nrel.gov/publications. U.S. Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…The technical potential for rooftop PV is 1,118 GW (Gagnon et al 2016), so there may be additional opportunities beyond the 190 GW deployed in this study (Prasanna et al 2021). Distributed wind has a similarly large technical and economic potential (McCabe et al 2022), as well as the potential to scale to 40 GW (Lantz et al 2016) from the 1.1 GW installed in 2020 (Orrell, Kazimierczuk, and Sheridan 2021).…”
Section: Text Box 4 the Role Of Distributed Resourcesmentioning
confidence: 95%
“…The technical potential for rooftop PV is 1,118 GW (Gagnon et al 2016), so there may be additional opportunities beyond the 190 GW deployed in this study (Prasanna et al 2021). Distributed wind has a similarly large technical and economic potential (McCabe et al 2022), as well as the potential to scale to 40 GW (Lantz et al 2016) from the 1.1 GW installed in 2020 (Orrell, Kazimierczuk, and Sheridan 2021).…”
Section: Text Box 4 the Role Of Distributed Resourcesmentioning
confidence: 95%
“…Dado el potencial de mercado en desarrollo en los Estados Unidos (McCabe et al 2022) y a nivel mundial, incluso en climas extremos como el del norte de Alaska y el del Caribe, las tecnologías eólicas distribuidas probablemente sean aplicables en muchas áreas de Puerto Rico, como lo indica el potencial de recursos de energía eólica, como se muestra en la Figura 55 (Sección 4.2, pág. 101).…”
Section: 521unclassified
“…This involves fitting a multiple linear regression with the following form (Equation 1): Where 𝑤 ! "# is the observed wind speed at the meteorological tower, 𝑤 %&' is the WTK estimate for the wind speed, 𝑑 %&' is the direction of the model data in degrees, h is the hour of the day (0-23), and m is the month of the year (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Values for the coefficients x0, x1, x2, x3, and x4 are fitted with least squares regression.…”
Section: Bias Correctionmentioning
confidence: 99%
“…In the realm of wind energy, distributed wind (DW) involves 10to 60-meter turbines appropriate for deployment in a broad range of application areas including residences, farms, industrial sites, and campuses. Recent studies have found a significant opportunity to utilize distributed wind to meet US energy needs [1]. Despite this significant opportunity, adoption of such technology is hindered by the cost of projects, confidence in the underlying technology and resources, and availability of incentives.…”
Section: Introductionmentioning
confidence: 99%